Developing pedagogical expertise in modern language learning and specific learning difficulties through collaborative and open educational practices. Issue 4 (2nd October 2017) - Gallardo, Matilde; Heiser, Sarah; Arias McLaughlin, Ximena
Abstract : This paper analyses teachers' engagement with collaborative and open educational practices to develop their pedagogical expertise in the field of modern language (ML) learning and specific learning difficulties (SpLD). The study analyses the findings of a staff development initiative at the Department of Languages, Open University, UK, in 2013, that aimed to support language teachers in distance learning to develop a better understanding of key issues in relation to MLs and adult learners with SpLD and dyslexia in particular. It discusses the motivational benefits of online collaboration for teachers' professional development and explains the implications of using a range of network-based tools to facilitate the construction of active shared learning and the joint production of open-access learning resources aimed at supporting adult language learners with SpLD in distance learning settings.